2017
DOI: 10.1155/2017/3549375
|View full text |Cite
|
Sign up to set email alerts
|

A Role of the ABCC4 Gene Polymorphism in Airway Inflammation of Asthmatics

Abstract: The ATP-binding cassette subfamily C member 4 gene encodes a transmembrane protein involved in the export of proinflammatory molecules, including leukotriene, prostaglandin, and sphingosine-1-phosphate across the plasma membrane. Those metabolites play important roles in asthma. We investigated the potential associations between ABCC4 gene polymorphisms and asthma phenotype. In total, 270 asthma patients and 120 normal healthy controls were enrolled for a genetic association study. Two polymorphisms (−1508A>G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 65 , 66 The functional impact of these variations, especially nonsynonymous polymorphisms, have been investigated in previous studies. 67 71 In genetic association studies of disease status and symptoms, SNPs or copy number variations within or around the ABCC4 gene have been shown to be associated with airway inflammation in asthmatic individuals, 68 unfavorable clinical outcomes in children with acute lymphoblastic leukemia, 69 patients with esophageal squamous cell carcinoma, 72 patients with chemotherapy-induced peripheral neuropathy, 73 and measures of pain symptoms in patients with lung cancer and acute post-radiotherapy pain. 74 , 75 However, none of these studies included the rs4773840 SNP or other SNPs that were in relatively strong LD with this SNP in our samples ( r 2 ≥ 0.8; Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“… 65 , 66 The functional impact of these variations, especially nonsynonymous polymorphisms, have been investigated in previous studies. 67 71 In genetic association studies of disease status and symptoms, SNPs or copy number variations within or around the ABCC4 gene have been shown to be associated with airway inflammation in asthmatic individuals, 68 unfavorable clinical outcomes in children with acute lymphoblastic leukemia, 69 patients with esophageal squamous cell carcinoma, 72 patients with chemotherapy-induced peripheral neuropathy, 73 and measures of pain symptoms in patients with lung cancer and acute post-radiotherapy pain. 74 , 75 However, none of these studies included the rs4773840 SNP or other SNPs that were in relatively strong LD with this SNP in our samples ( r 2 ≥ 0.8; Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Variant allele carriers of rs868853(C), which is located in the ABCC4 promoter, exhibited higher 2-AT+2-ATL levels than homozygous wild-type carriers (TT), and rs868853 was found to be an independent influence on plasma concentrations of 2-AT+2-ATL after adjusting for non-genetic factors by multiple linear regression. Palikhe et al showed asthma patients with the rs868853G allele had higher concentrations of asthma severity markers in blood and urine, and that the rs868853G SNP increased ABCC4 promoter transcriptional activity, suggesting that rs868853C may be associated with the transport of metabolites from immune cells (Palikhe et al, 2017). Additionally, carriers of the rs868853T allele were found to have a lower susceptibility to Kawasaki disease in a southern Chinese population (Che et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that variants of ABCC4 were associated with multiple disease susceptibilities. Palikhe et al found that the variants of ABCC4 (rs868853) were associated with airway inflammation in asthmatics [ 40 ], and Likanonsakul et al found that the ABCC4 4976C allele was associated with beta2-microglobulinuria in human immunodeficiency virus- (HIV-) infected patients in Thailand and showed that this difference may help identify patients at greater risk of developing tenofovir diisopropyl fumarate-induced kidney tubular dysfunction [ 41 ]. Variants of ABCC4 (rs9561778) showed a significant association with cyclophosphamide-induced adverse drug reactions in breast cancer patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%